A common dream: . Rehabilitation plan for the former Pelícana train station. Valle del Elqui, Chile (ARQUISUR Revista, 2022)
The former Pelícana train station is a earthen building that is located in the town of Pelícana in Valle del Elqui. Within the framework of a master's degree research and thanks to the research project Semilla Dicyt No 092090MP_ARQ of the Universidad de Santiago de Chile - Usach, it was raised to carry out a proposal for the rehabilitation of this abandoned space, revaluing it and putting it at the service of the needs of the sector. The study carried out responded to the characteristics of a projective type investigation, whose study events were: architectural deterioration and the needs of communal space. Research instruments were applied for the critical diagnosis of pathologies of the property and for the knowledge of the needs of common spaces by the local population, results analyzed with qualitative and quantitative techniques, respectively. Based on these preliminary results, the rehabilitation proposal was designed, which includes programs for sports, study, walking and meeting spaces. The investigation concludes in the development of an architectural rehabilitation plan for a building rooted in the sensitivity, history and identity of a locality, which has been consulted about its needs and interests in terms of the rehabilitation of this space, it is a plan that has highly gained feasibility, permanence and validity over time, which would guarantee the permanence of the ​​implicit architectural values in the building.
Keywords: architectural rehabilitation; earthen construction; deterioration in buildings; communal spaces; railway station